Randomized clinical trial of autologous skin cell suspension for accelerating re-epithelialization of split-thickness donor sites. Issue 7 (5th April 2017) - Hu, Z; Guo, D; Liu, P; Cao, X; Li, S; Zhu, J; Tang, B
Abstract: Background: Split-thickness skin graft (STSG) is used frequently, but may result in complications at the donor site. Rapid healing of donor-site wounds is critical to relieving morbidity. This study investigated whether autologous skin cell suspension could improve healing of STSG donor-site wounds. Methods: Between September 2014 and February 2016, patients requiring STSGs were randomized to receive autologous skin cell suspension plus hydrocolloid dressings (experimental group) or hydrocolloid dressings alone (control group) for the donor site. The primary outcome was time to complete re-epithelialization. Secondary outcomes included pain and itching scores measured on a visual analogue scale, and adverse events. Patients were followed for 12 weeks to evaluate quality of healing. Analysis was by intention to treat. Results: Some 106 patients were included, 53 in each group. Median time to complete re-epithelialization was 9·0 (95 per cent c.i. 8·3 to 9·7) days in the experimental group, compared with 13·0 (12·4 to 13·6) days in the control group ( P < 0·001). Overall postoperative pain and itching scores were similar in both groups. No between-group differences in treatment-related complications were observed. Both patients and observers were more satisfied with healing quality after autologous skin cell suspension had been used. Conclusion: The use of autologous skin cell suspension with hydrocolloid dressings accelerated epithelialization and improved healing quality of the donor site compared with hydrocolloid dressings alone. Registration number: UMIN000015000 (http://www.umin.ac.jp/ctr ). Abstract : Speeds healing